Cost Stickiness and Income Smoothing with Focus on Management Motives in Cement Industry - GholamReza Soleimani Amiri (Ph.D) (Shahid Bahonar University of Kerman, 2019)
Objective: Thisstudy shows cost stickiness and income smoothing in the cement industry occur in response to managerial caution and motives. The reason for choosing the cement industry is the specific nature of costs and production costs in this industry that may affect the managerial motives, and then, the management of profits. Methods: This research is descriptive and experimental and takes the financial data from 2007 to 2016. Assuming that the cement industry managers were susceptible to some misleading behaviors in financial reporting due to excess supply of cement in the domestic market over the study years, this study examined the relationship between cost stickiness and profit smoothing in this industry. Results: The results showed that there is no negative and significant relationship between cost stickiness and income smoothing in the cement industry, and that it may be resulted from management distorting behavior to reduce costs stickiness by income smoothing. The results also suggested that the two variables do not have negative and significant effect on each other. Conclusion: It is expected that there is negative relationship between the two managerial events. However, due to the certain conditions of the cement industry, this relationship did not observed.